Use of Visual Learning Media to Increase Student Learning Motivation - Katona, Bokarewa; Venkataragavan, Jensen; Nina, Erlandsson; Ulrika, Burmann; Björn, Oparina (World Psychology, 2022)
The development of the digitalization era today has a great impact on the world of education, this development can be seen from the many developments in learning media that can be used to increase student learning motivation. with increased motivation can foster students' confidence in this visual learning. One of the learning media used today is visual learning media. This study aims to determine the use of visual learning media to increase student motivation. The method used in this study is a quantitative method using Google Chrome and conducting in-depth interviews. The results of this study show how many digitalization learning media are used by educators to be able to improve the quality of student learning to be easier and better. this can make it easier for educators and students to be able to understand an ongoing learning between the two. Because with the help of this visual learning media, it will make learning interesting for students. with interesting learning it will make students enthusiastic in learning. The drawback of this study is that researchers cannot conduct interviews directly on the use of visual learning media used by educators to students, therefore researchers hope that future researchers can be better than on the current one.